Caliper simulation using computer for vocational and technical education - TOPTAŞ, ERSİN; GENÇ, GARİP; AKKUŞ, NİHAT (E D P SCIENCES, 2016)
In this study a caliper simulation was developed as computer application for using in the Vocational Education and Training ( VET) and Distance-based training. This simulation was developed for teaching the caliper as measurement tool based Metric and Whitworth measurement systems. The developed caliper simulation introduced in detail step by step as user guide. The vernier scales are simulated as 1/10, 1/20 and 1/50 for metric measurement system and 1/64, 1/128 and 1/1000 for Whitworth measurement system. This simulation can easily be download and setup as computer software. To the best of the authors' knowledge, this is the most important application for students to study everywhere they would like.
Keywords: Caliper training; technical education; vocational education; technical training; educational tool